Penggunaan Serbuk Eceng Gondok Teraktivasi HNO3 dan HCl dalam Menurunkan Kesadahan Air - S, Syamsudin; Budirman, Budirman; Batari, Andi Ayu Indriani (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Water hardness is caused by two variable metals or cations: calcium (Ca) and magnesium (Mg). One effective way to reduce hardness levels is to utilize water hyacinth powder. This study activated water hyacinth powder using nitric acid (HNO3) and hydrochloric acid (HCl). Water hyacinth contains functional groups that act as active groups in the adsorption process to capture cations that cause hardness. This experimental research tests the effectiveness of reducing water hardness using water hyacinth powder activated with HNO3 and HCl in a dipping bag system. The results showed that water hyacinth powder activated with nitric acid reduced water hardness levels with an average decrease of 499.6 mg/l.Meanwhile, water hyacinth powder activated with hydrochloric acid reduced water hardness levels with an average decrease of 451.3 mg/l. The combination of nitric acid and hydrochloric acid activation gave an average decrease of 510.05 mg/l. This study concludes that water hyacinth powder activated with hydrochloric acid individually is more effective than activating a combination of nitric acid and hydrochloric acid in reducing water hardness. For communities facing water hardness problems, using activated water hyacinth powder can be a promising alternative. The potential of water hyacinth as a hardness-reducing agent provides new opportunities in the effort to provide clean water that is more affordable and environmentally friendly. Keywords: Hardness; Hyacinth Powder; Activation